2016
DOI: 10.3390/app6030076
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Machining Stability of a Milling Machine with Hybrid Guideway Systems

Abstract: This study was aimed to investigate the machining stability of a horizontal milling machine with hybrid guideway systems by finite element method. To this purpose, we first created finite element model of the milling machine with the introduction of the contact stiffness defined at the sliding and rolling interfaces, respectively. Also, the motorized built-in spindle model was created and implemented in the whole machine model. Results of finite element simulations reveal that linear guides with different prel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…1) was used. A representative compliance [Wöste 2019, Hung 2016 was synthesized by applying a specific, simulation-based design of a flexure hinge module. The interrupted cut was realized by implementing notches in a workpiece consisting of the aluminum alloy EN AW-7075.…”
Section: Interrupted Cut and Specific Compliancementioning
confidence: 99%
“…1) was used. A representative compliance [Wöste 2019, Hung 2016 was synthesized by applying a specific, simulation-based design of a flexure hinge module. The interrupted cut was realized by implementing notches in a workpiece consisting of the aluminum alloy EN AW-7075.…”
Section: Interrupted Cut and Specific Compliancementioning
confidence: 99%
“…Research studies [2][3][4] have shown that a rolling guide exhibits different vibration characteristics, depending on the preload applied on the rolling elements. The interface characteristic of mechanical components with rolling elements has been shown to be an important factor that affects the static and dynamic characteristics of the machine tool [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…These efforts led to joint stiffness modeling and stiffness identification of the robot, and there are some groups of stiffness identification algorithms. For example, the finite elements analysis (FEA) method constructs the physical model based on many of finite elements and the corresponding relative stiffness matrices [4][5][6]. Mekaouche presented a method of evaluating the relationship between a numerical tool and a general stiffness map of the robot based on FEA [7].…”
Section: Introductionmentioning
confidence: 99%